Pengaturan Kondisi Kelas Dan Iklim Belajar di IV SD Muhammadiyah Alternatif 2 Kota Magelang - Rani, Vidya Puspita (Prosiding University Research Colloquium, 2021)
This study aims to observe, observe how the implementation of classroom management in SD Mutual 2 Magelang City. The research method used is a qualitative method with observations and interviews in the school environment. The results of this study indicate that the classroom management at SD Mutual is very good, with neatly arranged rooms and decorations that make children enthusiastic about learning. The implementation in managing classes in schools is by making the class full of student work, prioritizing student activity during the teaching and learning process, using a skills approach in learning so that students can master skills in managing the class, by rolling out student seating arrangements who are already able mastering learning is moved to the back seat while students who have not mastered learning are moved to sit in the front to focus more on the material being conveyed, create learning media from student skills and students who work together to achieve learning goals that create a classroom atmosphere and atmosphere learning to be fun and conducive.